2020
DOI: 10.1146/annurev-pathmechdis-012419-032824
|View full text |Cite
|
Sign up to set email alerts
|

Liver Progenitors and Adult Cell Plasticity in Hepatic Injury and Repair: Knowns and Unknowns

Abstract: The liver is a complex organ performing numerous vital physiological functions. For that reason, it possesses immense regenerative potential. The capacity for repair is largely attributable to the ability of its differentiated epithelial cells, hepatocytes and biliary epithelial cells, to proliferate after injury. However, in cases of extreme acute injury or prolonged chronic insult, the liver may fail to regenerate or do so suboptimally. This often results in life-threatening end-stage liver disease for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 155 publications
(194 reference statements)
3
101
0
1
Order By: Relevance
“…There have been several studies demonstrating the critical roles for DNMT in liver cancer development and maintenance (31,(44)(45)(46); most of studies showed that pharmacologic DNMT inhibition leads to hypomethylation of the promoters of various tumor suppressors such as p16INK4a, FoxM1, TP53, PTEN, and others (47), which typically induces death of malignant cells. At the same time, like other epigenetic regulators (20,48,49), DNMT1 plays critical roles in various cell fate switches including HC-to-BEC conversion (29)(30)(31)(32)50). Likewise, we also found that DNMT1 inhibition impairs AN-mediated HC-to-BEC conversion, thereby completely abrogating HC-driven murine ICC development.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…There have been several studies demonstrating the critical roles for DNMT in liver cancer development and maintenance (31,(44)(45)(46); most of studies showed that pharmacologic DNMT inhibition leads to hypomethylation of the promoters of various tumor suppressors such as p16INK4a, FoxM1, TP53, PTEN, and others (47), which typically induces death of malignant cells. At the same time, like other epigenetic regulators (20,48,49), DNMT1 plays critical roles in various cell fate switches including HC-to-BEC conversion (29)(30)(31)(32)50). Likewise, we also found that DNMT1 inhibition impairs AN-mediated HC-to-BEC conversion, thereby completely abrogating HC-driven murine ICC development.…”
Section: Discussionsupporting
confidence: 59%
“…IHC confirmed the ICCs to be positive for biliary marker pan-cytokeratin (panCK), HA tag (AKT), MYC tag (NICD), and SOX9 where expected ( Fig.1F-H). Given the critical role for SOX9 downstream of Notch signaling in HC-to-BEC conversion in liver injury (18,20), we next generated AKT-SOX9 model by HDTVI of myr-Akt (HA tag) and Sox9. Interestingly, no tumors were observed at 5-weeks post-injection, either macroscopically or microscopically ( Transcriptome analysis of HC-derived ICC in AKT-NICD model reveals significant similarity to a subset of human ICCs.…”
Section: Myristoylated-akt Cooperates With Nicd But Not Sox9 In Inducmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cell populations participate in this process. These are mainly hepatocytes, but also multiple multipotent and bipotent stem cell populations expressing endodermal or mesenchymal markers [15][16][17][18][19][20].…”
Section: Liver Development and Regenerationmentioning
confidence: 99%
“…However, if hepatocytes are damaged too extensively to participate in the liver repair process, liver regeneration occurs via differentiation of (facultative) hepatocyte progenitor/stem cells. The origin of these progenitors remains not fully understood, and likely includes liver progenitor cells, cholangiocytes, and intermediary hepatocytes (recently reviewed in [1]). However, if liver damage persists, or gives rise to liver fibrosis and cirrhosis, none of the above mechanisms can repair lost hepatocytes, giving rise to liver failure.…”
Section: Introductionmentioning
confidence: 99%